Culinary Sustainability: Exploring The Potential Of Manihot Esculenta In Innovative Production Using The Au Bain Marie Technique: Culinary Sustainability: "Menggali Potensi Manihot Esculenta Dalam Inovatif Produksi Menggunakan Teknik Au Bain Marie - Tatik Sriwulandari; Nisa Rahmaniyah Utami; Saleha (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to explore the potential of Manihot esculenta (cassava) as a sustainable food source through innovative production techniques utilizing the au bain marie method. Manihot esculenta, a primary source of carbohydrates in many developing countries, offers environmental benefits due to its ability to thrive in diverse soil conditions and extreme weather. This research examines how the use of the au bain marie technique—which prioritizes indirect heating to preserve nutritional quality—can enhance the culinary value of cassava while supporting local food sustainability efforts. The methodology includes experimental production of various cassava-based dishes using the au bain marie method, along with an analysis of sensory characteristics, nutritional value, and economic feasibility. The results show that the au bain marie technique can retain essential nutrients in cassava while improving its texture and flavor, making it an appealing alternative in modern cuisine. These findings underscore the importance of innovation in processing local food ingredients to enhance culinary sustainability and promote the diversification of environmentally friendly food products.